Contribution of sustainable food house area to income and family food security in Tulang Bawang Barat, Lampung Province. Issue 1 (April 2021) - Rangga, K K; Pujiana, T; Syarief, Y A; Viantimala, B; Mutolib, A; Adipathy, Dina Arini
Abstract: This study aims to determine the implementation of the sustainable food house area program, contribution of the program to family income of farmer women's group, and analyze the food security of KWT members in Tulang Bawang Barat Regency. The research was conducted in five groups of women farmers in Margodadi, Marga Kencana, Tirta Makmur, Tirta Kencana, and Mulya Asri Villages. Data were collected in December 2019. Data were collected using survey methods and direct interviews in the field. The sampling method was carried out deliberately (purposive sampling); as many as 62 people were interviewed by visiting the respondent's house. The results showed that the implementation of the program was seen from the development of village nurseries, development of demonstration plot plots, and development of farmer women's group members' yards. The income women's group's income the yard utilization program for one year ranges from IDR 2, 565, 600 - IDR 6, 930, 000. Family food security of KWT members subjectively categorized in the medium category from the adequacy of family food availability of KWT members, food distribution in the family is quite good, and aspects of family food consumption are also quite good. The affordability of families to get food is quite relatively. Women farmer groups' knowledge is already good about the food the body needs in the right composition. It is present in all types of food that are useful for health, in consuming family food by taking into account the quality and quantity of food they consume..